Effects of obesity, metabolic syndrome, and non‐alcoholic or alcoholic elevated liver enzymes on incidence of diabetes following lifestyle intervention: A subanalysis of the J‐DOIT1. Issue 1 (21st January 2020) - Sakane, Naoki; Kotani, Kazuhiko; Suganuma, Akiko; Takahashi, Kaoru; Sato, Juichi; Suzuki, Sadao; Izumi, Kazuo; Kato, Masayuki; Noda, Mitsuhiko; Nirengi, Shinsuke; Kuzuya, Hideshi
Abstract: Objectives: Using annual health check‐up data, the aim of this study was to identify target populations for lifestyle interventions to effectively prevent diabetes in a real‐world setting. Methods: The Japan Diabetes Outcome Intervention Trial‐1, a prospective, cluster‐randomized controlled trial, was launched to test if year‐long telephone‐delivered lifestyle support by health professionals can prevent the development of type 2 diabetes (T2D) in people with impaired fasting glucose (IFG) identified at health check‐ups. A total of 2607 participants aged 20‐65 years with IFG were randomized to an intervention arm (n = 1240) or a control arm (n = 1367). We performed subgroup analysis to examine the effects of the intervention on the incidence of T2D in participants with body mass index (BMI) ≥25, metabolic syndrome (MetS), and non‐alcoholic or alcoholic elevated liver enzymes at the baseline. Cox regression analysis adjusted for sex was used to calculate the hazard ratios (HRs). Results: In addition to IFG, the presence of BMI ≥25, MetS, and elevated liver enzymes increased the incidence of diabetes by two‐ or three‐fold. During a median follow‐up period of 4.9 years, only the non‐alcoholic elevated liver enzyme group showed a low incidence rate owing to lifestyle interventions (adjusted HR: 0.42, 95% confidence interval: 0.18‐0.98). Conclusion: The results suggest that people who have IFG and non‐alcoholic elevated liver enzymes are a good target population for lifestyle interventions to effectively reduce the incidence of diabetes in a real‐world setting.